Evaluasi Penerapan Keselamatan dan Kesehatan Kerja Pada Gedung Perawatan Jiwa RSUD Nagan Raya - Chaira Chaira; Zakia zakia (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2018)
The construction industry is a sector that has a high level of risk both in terms of business risks, occupational health and safety risks. The lack of OHS implementation, resulting in increased work accidents in construction projects. OHS in the Construction Industry needs special attention, it can cause harm to workers, employers, the government and the community, which can be human casualties, property damage and the environment around the project. This study aims to determine the application of OSH in the New Building Care project at Nagan Raya Hospital and to determine the factors that influence OSH in the project. OSH evaluation is carried out by giving questionnaires to the project implementers then performed univariate and bivariate analysis to determine the relationship between variables. The number of respondents 25 people. The results obtained are the most dominant age 16-20 years and at least 42-44 years. The highest level of education in the group without school and the lowest S. The average work period of workers is 10-15 years by 40%. The results of univariate analysis, the frequency distribution for answers "less" is 61.5% for site managers, as well as implementers who answer "no" with a frequency of 60.0% and supervisors 41.7%. This indicates the lack of application of OSH to the project concerned. This is due to the lack of knowledge about OSH management systems and concepts both from the site manager as the project manager, implementer and supervisor so that workers do not get a proper understanding of the OSH.